1997
DOI: 10.1093/ortho/24.3.237
|View full text |Cite
|
Sign up to set email alerts
|

Electrothermal debonding of ceramic brackets: an ex vivo study.

Abstract: The shear forces necessary to remove ceramic brackets from human premolar teeth using mechanical and electrothermal debonding techniques were compared and the post-debond enamel characteristics were evaluated. The temperature rise in the pulp cavity during electrothermal debonding was recorded. The samples were tested sequentially on a shear jig attached to an Instron Universal Testing Machine. The results indicate that removal of ceramic brackets with an electrothermal debonder requires less force than with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
4
0
3
Order By: Relevance
“…Debonding brackets using electrothermal devices have already been reported in the literature 17-19 and rebonding brackets repeatedly following debracketing have also been reported. 20 However, no previous study has reported the bracket repositioning procedure performed likely as in the present study.…”
Section: Discussionmentioning
confidence: 91%
“…Debonding brackets using electrothermal devices have already been reported in the literature 17-19 and rebonding brackets repeatedly following debracketing have also been reported. 20 However, no previous study has reported the bracket repositioning procedure performed likely as in the present study.…”
Section: Discussionmentioning
confidence: 91%
“…[1][2] Ceramic brackets are being used extensively in modern orthodontic practice because of their higher esthetics and greater bond strengths over conventional metallic brackets. [3][4][5][6] During the course of treatment there is a need of bonding the brackets with bonding agent that will have adequate bond strength between the tooth and bracket so that it will resist force applied to the teeth. [7][8] The term debonding refers to removal of orthodontic attachments and residual adhesive from the enamel surfaces that restore as closely as possible to its pre-treatment condition without inducing iatrogenic enamel damage.…”
Section: Introductionmentioning
confidence: 99%
“…• Amolecimento do compósito por métodos eletrotérmicos sendo que não há segurança neste procedimento, pois há grande risco de necrose pulpar, devido ao alto grau de aquecimento produzido (Rueggeberg e Lockwood, 1990;Dovgan et al, 1995;Takla et al, 1995;Vargas, 1996;Kearns et al, 1997);…”
Section: Lista De Abreviaturasunclassified
“…Para que se estudem esses possíveis danos aos tecidos dentais, alguns autores avaliaram a estrutura do esmalte, o calor que atinge a câmara pulpar (Rueggeberg e Lockwood, 1990;Rueggeberg e Lockwood, 1992;Kearns et al, 1997;Ma et al, 1997;Azzeh e Feldon, 2003;Goodis et al, 2004;Feldon et al, 2010;Dostalova et al, 2011;Nalbantgil et al, 2011), em animais (Wang et al, 2009) e humanos (Mercadante et al, 2003) após a aplicação para remoção de bráquetes, demonstrando ser um procedimento viável. Ao se utilizar dentes extraídos, alguns autores têm utilizado a imersão do dente em água a 37º C, para reduzir o calor armazenado durante a irradiação, na tentativa de reproduzir a situação clínca do dente inserido no alvéolo (Macri, 2002, Lin et al, 2010.…”
Section: Lista De Abreviaturasunclassified
See 1 more Smart Citation